Development of a PBPK-based health risk assessment framework for exposure to cerium, gold, silver and titanium engineered nanoparticles - Voyi, Kuku V.V. (University of Pretoria, 2020)
Thesis (PhD (Public Health))--University of Pretoria, 2020.